1988
DOI: 10.1089/dna.1.1988.7.347
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Alpha2(I), Alpha1(III), and Alpha2(V) Collagen mRNAs by Estradiol in the Immature Rat Uterus

Abstract: We show that mRNAs for alpha 2(I), alpha 1(III), and alpha 2(V) collagens are regulated by estradiol in the immature rat uterus. Clones for alpha 2(I) and alpha 1(III) collagen were induced in a cDNA library prepared from estradiol-stimulated rat uterine mRNA. Alpha 2(I) collagen cDNA was identified by its characteristic hybridization pattern on Northern blots and hybridization to known probes. The sequence of alpha 1(III) collagen cDNA showed 91% amino acid sequence homology with the corresponding 525-nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…COL3A1 mRNA was abundant during proestrus (day 16 cycle), suggesting that estrogen up-regulates COL3A1 expression in ovine uterine stromal cells. This is consistent with estrogen stimulation of expression of collagen types I, III, and V in rat uteri (Frankel et al 1988) and collagen types I, III, and VI in uterine stromal cells of postmenopausal women (Iwahashi et al 1997). COL3A1 is the collagen type that increases tensile strength (van der Rest & Garrone 1991, Burgeson & Nimni 1992, Aumailley & Gayraud 1998.…”
Section: P 4 and Ifnt-regulated Genes In Ovine Uterisupporting
confidence: 69%
“…COL3A1 mRNA was abundant during proestrus (day 16 cycle), suggesting that estrogen up-regulates COL3A1 expression in ovine uterine stromal cells. This is consistent with estrogen stimulation of expression of collagen types I, III, and V in rat uteri (Frankel et al 1988) and collagen types I, III, and VI in uterine stromal cells of postmenopausal women (Iwahashi et al 1997). COL3A1 is the collagen type that increases tensile strength (van der Rest & Garrone 1991, Burgeson & Nimni 1992, Aumailley & Gayraud 1998.…”
Section: P 4 and Ifnt-regulated Genes In Ovine Uterisupporting
confidence: 69%
“…Furthermore, Woessner (1979) found that injection with E 2 causes a decrease in uterine collagenase activity that is correlated with the rate of collagen breakdown. Frankel et al (1988) found that E 2 induces alpha 2 (I) and alpha 1 (III) collagen mRNAs in the immature rat uterus, and Dyer et al (1980) reported that E 2 stimulates both synthesis and degradation of collagen in the ovariectomized rat uterus. It therefore seems that the effect of estrogen on collagen metabolism in the uterus changes according to the physiological state of the animals.…”
Section: Discussionmentioning
confidence: 99%
“…The amplification by PCR was performed with the use of 1 L of cDNA and 2 L each of 2.5 mmol/L coding and noncoding oligonucleotide primers and Platinum PCR Supermix (Life Technologies). The primer sequences were as follows: TGF-␤1: coding 5Ј-ACG CCT GAG TGG CTG TCT TTT-3Ј and noncoding 5Ј-ACG TGG AGT TTG TTA TCT TTG-3Ј 18 ; ␤-actin: coding 5Ј-GAT CTG GCA CCA CAC CTT CTA-3Ј and noncoding 5Ј-GCA GGA TGG CGT GAG GGA GAG-3Ј 19 ; collagen I: coding 5Ј-CCC ACG TAG GTG TCC TAA AGT-3Ј and noncoding 5Ј-CCG TGG TGCTAAAATAATAAA-3Ј 20 ; fibronectin: coding 5Ј-ATG ATG AGG TGC ACG TGT GT-3Ј and noncoding 5Ј-GAT GGG GTC ACA TTT CCA TC-3Ј 21 ; MMP-2: coding 5Ј-GTG CTG AAG GAC ACA CTA AA-3Ј and noncoding 5Ј-TTG CCA TCC TTC TTT TCA AA-3Ј 22 ; TIMP-2: coding 5Ј-AAA CGA CAC TTA TGG CAA AC-3Ј and noncoding 5Ј-ACA GGA AGC GTC ACT TCT CT-3Ј. 23 For this semiquantitative estimation of gene expression, we performed cycle analysis for each primer pair to determine the cycle number for optimal amplification.…”
Section: Detection Of Mrna By Reverse Transcription and Polymerase Chmentioning
confidence: 99%